The Investigation of Brain/Behavioral Systems in Narcotic abusers in Comparison with Stimulant Abusers - Majid mahmoudAlilou; Parastoo Amiri (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The aim of the present study was to investigate the differences in the scores relating to brain/behavioral systems in two groups of narcotic and stimulant substance abusers. Method: An Expos Facto research design was used in this study. The study sample consisted of 200 drug-dependent male participants who were selected from the addicts referring to authorized treatment centers and inpatient rehab camps in Tabriz through convenience sampling method. The researcher used behavioral activation system (BAS) and behavioral inhibition system (BIS) scales developed by Carver and White (1994). Results: The results revealed that behavioral activation system scores were different in narcotic and stimulant substance abusers and stimulant substance abusers outperformed their narcotic counterparts in BAS. However, there was no significant difference between the two groups in BIS scores. Conclusion: The results enjoy practical implications.